The Effect of Social Media Marketing on Purchase Intention Through Brand Awareness on Sociolla E-Commerce Users in Pekanbaru City - Sitorus, Kristina Permata Sari; Wijayanto, Gatot; Nursanti, Aida (Basecamp Economics PubMed, 2024)
This study aims to determine the effect of social media marketing on buying interest through brand awareness on sociolla e-commerce users in pekanbaru city. The sampling technique used purposive sampling with non-probability sampling. Data was obtained by distributing questionnaires to 120 respondents. The approach used in this research is quantitative and uses the SEM-PLS model and SmartPls 4.0 software as a tool for this research. The results of this study indicate that: there is a positive and significant influence of social media marketing on brand awareness on Sociolla e-commerce users in Pekanbaru City, there is a positive and significant influence of brand awareness on buying interest in Sociolla e-commerce users in Pekanbaru City, there is a positive and significant influence of social media marketing on buying interest in Sociolla e-commerce users in Pekanbaru City, there is a positive and significant influence of social media marketing on buying interest through brand awareness on Sociolla e-commerce users in Pekanbaru City. For further researchers, it is hoped that this research will become a reference and analyze the time period and develop more research.